2014
DOI: 10.18632/oncotarget.2617
|View full text |Cite
|
Sign up to set email alerts
|

Metformin repositioning as antitumoral agent: selective antiproliferative effects in human glioblastoma stem cells, via inhibition of CLIC1-mediated ion current

Abstract: Epidemiological and preclinical studies propose that metformin, a first-line drug for type-2 diabetes, exerts direct antitumor activity. Although several clinical trials are ongoing, the molecular mechanisms of this effect are unknown.Here we show that chloride intracellular channel-1 (CLIC1) is a direct target of metformin in human glioblastoma cells. Metformin exposure induces antiproliferative effects in cancer stem cell-enriched cultures, isolated from three individual WHO grade IV human glioblastomas. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
170
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(182 citation statements)
references
References 67 publications
(108 reference statements)
8
170
1
3
Order By: Relevance
“…Metformin induced apoptosis in the T98G cell line in a concentration-dependent manner (Ucbek et al 2014). Gritti et al (2014) demonstrated that chloride intracellular channel-1 (CLIC1) is a direct target of metformin in human glioblastoma cells. Metformin blocked proliferation in cancer stem cell-enriched cultures, isolated from three individual WHO grade IV human GBMs (Gritti et al 2014).…”
Section: Metformin Efficacy In Glioblastoma: Basic Science Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Metformin induced apoptosis in the T98G cell line in a concentration-dependent manner (Ucbek et al 2014). Gritti et al (2014) demonstrated that chloride intracellular channel-1 (CLIC1) is a direct target of metformin in human glioblastoma cells. Metformin blocked proliferation in cancer stem cell-enriched cultures, isolated from three individual WHO grade IV human GBMs (Gritti et al 2014).…”
Section: Metformin Efficacy In Glioblastoma: Basic Science Evidencementioning
confidence: 99%
“…Gritti et al (2014) demonstrated that chloride intracellular channel-1 (CLIC1) is a direct target of metformin in human glioblastoma cells. Metformin blocked proliferation in cancer stem cell-enriched cultures, isolated from three individual WHO grade IV human GBMs (Gritti et al 2014). These actions accompanied to metformin-inhibition of a chloride current which is dependent on functional activity of CLIC1 (Gritti et al 2014).…”
Section: Metformin Efficacy In Glioblastoma: Basic Science Evidencementioning
confidence: 99%
“…Ионный канал CLIC1 пре-имущественно активен в течение G1-S-фазы клеточного цикла [6]. Хлорные каналы (CLIC) могут быть активирова-ны внеклеточными лигандами, внутриклеточными ионами Са, цАМФ, G-белками, механическим растяжением и по-тенциалом.…”
Section: влияние метформина на внутриклеточные каналыunclassified
“…Также описано, что при-менение метформина снижает заболеваемость раком поджелудочной железы [5]. Примечательно, что авторы указывают на прямую противоопухолевую активность метформина [6], мишенью для которого являются внутри-клеточные хлорные каналы в клетках глиобластомы.…”
unclassified
“…The analysis not only confirmed regulation of targets previously shown to be controlled at the mRNA level (77,(82)(83)(84), but also identified proteins not previously associated with pregnancy-induced β cell expansion. Two examples are stathmin 1 and nuclear chloride ion channel 1, which have known roles in the regulation of cell proliferation and are being evaluated as drug targets in cancer (85)(86)(87)(88). While follow-up studies will be necessary, this study highlights the importance of global approaches to identify novel molecular targets for enhancing β cell proliferation.…”
Section: Introductionmentioning
confidence: 99%